ANTESEDEN DAN KONSEKUENSI EKUITAS MEREK DALAM INDUSTRI LABORATORIUM KLINIK - Bella Esty Pratiwi; Waluyo Budi Atmoko; Nang Among Budiadi (Conference on Innovation in Health, Accounting and Management Sciences (CIHAMS), 2020)
The aim of the research was tested the effect of brand equity on consumer response. Good consumer response can increase the brand equity of the clinical laborator y, thereby being able to strengthen the customers intention to re-conduct a health check. The Data obtained through questionnaires distributed online, consisting of five Surakarta cluster areas namely Jebres, Laweyan, Banjarsari, Pasar kliwon, Serengan. Sampling technique used was non probability sampling with a population of 200 respondents in the Budi sehat clinic laborator y in Surakarta. Hypothesis test using by SEM. The study found results: (1) brand image has a significant effect on brand equity, (2) brand equity has a significant effect on brand preference, (3) brand equity has asignificant effect on revicite intention, (4) brand awareness has no effect on brand equity, (5) perceived qualit y has no effect on brand equity, and (6) brand loyalty has no effect on brand equity.